(untitled) - Hoover, Thomas (New York, 1977)
ZEN CULTURE, concerned as it is with the process of perception as much as with actual works of art, can open our sense so that we experience anew the arts of both East and West, ancient and modern.
Keywords: Nhật Bản,Japan; Nền văn minh,Ảnh hưởng của Thiền tông,Civilization,Zen influences